EKSISTENSI KONSEP MASLAHAT TERHADAP PARADIGMA FIKIH FEMINIS MUSLIM TENTANG HAK DAN KEWAJIBAN SUAMI ISTERI - Agus Hermanto (Nizham Jurnal Studi Keislaman, 2019)
The concept of maslahat is one of the theories that exists in addressing contemporary cases, which in this case are the rights and obligations of husband and wife. Paradigm which says that the husband is the head of the household and the wife is a housewife is quite disturbing Muslim feminists to reinterpret and reconstruct by considering the mission of justice, equality, democracy and mu'asyarah bi al-ma'ruf, because the reality today is that a wife does not only helps in household matters, but more than that it also helps in matters of maintenance, the meaning of the head of the household must also instill the values ​​of togetherness, protect each other, support each other and work together to become good partners so that this paradigm must be straightened out for the benefit.